Influence of Test Protocol on Filtration Efficiency of Medical Face Mask Material - Aurélie Joubert; Ala Bouhanguel; Yves Andrès; Laurence Le Coq (Aerosol and Air Quality Research)
Abstract Medical face masks are an efficient protective barrier against the propagation of bacteria and viruses in societies. The current European standard focuses on the bacterial filtration efficiency of the filtering material for a mean particle size of 3.0 µm in terms of droplets that are exhaled, but viruses that are inhaled can be transported by particles of sub-micron size. The filtration efficiency of medical face mask material was evaluated in a bench test from both unused charged and discharged masks. Several polydisperse test aerosols were used - DEHS, alumina, HOLI, NaCl, Staphylococcus epidermidis and Emesvirus zinderi (MS2) - produced by liquid atomization and/or powder dispersion, and sized by optical and aerodynamic counters or cascade impactors. The results have shown that the particle size distribution and charges for a given type of aerosol can differ depending on the generator used, in particular the wet or dry nature of generation. The results in the sub-micron size range for charged face mask material showed that the filtration efficiency of neutral aerosols was lower than that of charged aerosols due to the electrostatic forces, e.g., 92% versus 99% efficiency for DEHS and alumina respectively for a mean aerodynamic diameter of 0.6 µm. With the discharged face mask material, the filtration efficiency was degraded in the sub-micron size range for all types of aerosol tested: e.g., 30% versus 65% efficiency for a mean optical diameter of 0.25 µm respectively for DEHS and alumina. For particle sizes > 3 µm, the results indicated that the nature of the aerosol has little influence because particle collection is dominated by impaction and interception mechanisms. The tests with MS2 virus demonstrated a good fit with NaCl filtration efficiency expressed in aerodynamic diameters over a range between 0.65 and > 7 µm, for charged and discharged medical face mask materials.